1999
DOI: 10.1089/clm.1999.17.165
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG Laser Influence on Sound Dentin Bond Strength

Abstract: Based on the results obtained, one can conclude that group 1 (without laser) and group 3 (laser after bonding) had similar results, both higher than those observed for group 2 (laser before bonding). These results indicate that more research is needed about how a hybrid layer is formed when laser radiation is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 28 publications
3
16
1
6
Order By: Relevance
“…The development of this new substrate explains why all of the groups irradiated by laser in this study showed a substantial increase in bond strength. This is in agreement with Matos and others 5 and Matos and others, 6 who evaluated Nd:YAG irradiation before and after adhesive application and concluded that the best results were observed when laser was used after the adhesive system application. According to Dayem and others, 18 treatment of the acid-etched dentin with Nd:YAG laser led to the significantly increased penetration depth of the adhesive bonding system into dentin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The development of this new substrate explains why all of the groups irradiated by laser in this study showed a substantial increase in bond strength. This is in agreement with Matos and others 5 and Matos and others, 6 who evaluated Nd:YAG irradiation before and after adhesive application and concluded that the best results were observed when laser was used after the adhesive system application. According to Dayem and others, 18 treatment of the acid-etched dentin with Nd:YAG laser led to the significantly increased penetration depth of the adhesive bonding system into dentin.…”
Section: Discussionsupporting
confidence: 91%
“…3 Although most researchers have found significantly higher bond strength values for adhesive systems that received Nd:YAG irradiation prior to polymerization, most of the studies investigated total-etch adhesives bonded to dentin. [4][5][6] The influence of laser irradiation on self-etch adhesives has not yet been adequately evaluated, especially on enamel.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations also concluded that bond strength of teeth treated with laser irradiation before bonding was weaker than that of teeth in the control group. 5,28,36 Previous studies on teeth conditioned by laser treatment confirm the results of our study. The control groups treated conventionally with adhesive systems attained the highest bond strengths.…”
Section: Discussionsupporting
confidence: 91%
“…The surfaces appeared as an amorphous, nonhomogenous structure. Our findings can be explained by the study by Matos and Ceballos 19,28 on the lacking formation of a hybrid layer after laser irradiation and thereby the lower bond strength. In comparison, the SEM images of samples treated with laser plus phosphorous acid revealed a homogenous surface ( Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 52%
“…The idea of association of laser with adhesive system for protection against erosion and abrasion on enamel emerged from the good results of studies using this technique to increase the bond strength of composite JCDP restorations. 20,21,38 That improvement is due to a permanent physical change in the dental substrate, which was fused with the resinous monomers, creating a new tissue composed of crystallized hydroxyapatite in the presence of monomers, improving the mechanical and chemical binding of the substrate to adhesives. 21,39 Based on those studies, it was assumed that a new substrate could increase the retention of the adhesive and its protective effect on erosion and abrasion.…”
mentioning
confidence: 99%